Plasma 8-Hydroxydeoxyguanosine, 4-Hydroxynonenal and Selenium in Hepatitis B Virus-Infected Adults in Ibadan, Nigeria - Orimadegun, Bose Eta; Diekola, Uswat Opeyemi; Akande, Kolawole Oluseyi; Anetor, John Ibhagbemien (Asian Pacific Journal of Environment and Cancer, 2024)
Introduction: Hepatitis B Virus (HBV) infection is a significant global health challenge, particularly in Sub-Saharan Africa, including Nigeria. Reactive oxidative species (ROS) generated during HBV replication contribute to redox imbalance, leading to oxidative stress. However, data on the levels of oxidative stress markers in Nigerians infected with HBV is scarce. This study aimed to investigate plasma levels of oxidative stress markers [8-hydroxydeoxyguanosine (8-OHdG) and 4-hydroxynonenal (4-HNE)] and the trace element, selenium, in HBV-infected adults in Ibadan, Nigeria. Materials and Methods: In a case-control study, 40 HBV-infected patients served as cases, and 40 HBV-uninfected patients served as controls. Anthropometric data were collected, and plasma 8-OHdG and 4-HNE were determined using the ELISA method. Selenium was determined using atomic absorption spectrophotometry. Data were analysed using descriptive, t-test, and Pearson correlation statistics at p = 0.05. Results: The mean ages of HBV-infected and uninfected individuals were 35.3±1.5 and 36.0±1.5 years, respectively. The level of 4-HNE was not significantly different between HBV-infected (2.2±1.7 ng/ml) and uninfected (1.8±1.3 ng/ml). There was also no significant difference in 8-OHdG levels between HBV-infected (4.1±2.4 ng/ml) and uninfected (3.6±1.8 ng/ml). However, in HBV-infected patients, 8-OHdG levels showed a significant positive correlation with 4-HNE (r =0.320, p =0.044). Selenium levels were also significantly higher in HBV-infected (78.4±25.4 ug/dl) than uninfected (35.6±11.4 ug/dl). Conclusion: The levels of markers of lipid peroxidation and DNA oxidation were similar in HBV-infected and uninfected participants, but selenium, the key component of the potent antioxidant glutathione peroxidase was more than double in the infected group. It is plausible that the protective effect of Se may have spared the other markers of oxidative damage. Further studies are needed to elucidate these preliminary findings.